Blockchain angels or demons of a free international order - Rossitsa Yalamova (OrdnungsPolitisches Portal (OPO), 2019)
"Decentralization and Democratization" is the main promise behind the distributed ledger technology that attracted enthusiasts looking for ways to prop our ailing global socio-economic system. Not surprisingly its best known application "Bitcoin" comes as the "panacea" against the worst offender in the neoliberal order, the Financial Industry. Trends, fads and myths about blockchain technology fuel the imagination allowing for proliferation of hypes and disappointment. This paper offers a discussion of possible blockchain applications for polycentric governance of socio-economic systems in light of building sustainability and resilience. On the opposite side I will analyze the possibility for misuse (e.g. the Internet of Things) of the technology to build ever stronger centralized control system lacking adaptive capacity and leading to total collapse.
Keywords: 330; Adaptive Systems; Blockchain; Globalization; Collapse of Complex Societies